The efficacy and safety of direct-acting antiviral regimens for end-stage renal disease patients with HCV infection: a systematic review and network meta-analysis - Chen, Ruochan; Xiong, Yinghui; Zeng, Yanyang; Wang, Xiaolei; Xiao, Yinzong; Zheng, Yixiang (Frontiers in Public Health, 2023)
Background Hepatitis C virus (HCV) infection is an independent risk factor associated with adverse outcomes in patients with end-stage renal disease (ESRD). Due to the wide variety of direct-acting antiviral regimens (DAAs) and the factor of renal insufficiency, careless selection of anti-hepatitis C treatment can lead to treatment failure and safety problems. The integrated evidence for optimized therapies for these patients is lacking. This study would conduct comparisons of different DAAs and facilitate clinical decision-making. Methods We conducted a systematic literature search in multiple databases (PubMed, Ovid, Embase, Cochrane Library, and Web of Science) up to 7 August 2023. Study data that contained patient characteristics, study design, treatment regimens, intention-to-treat sustained virologic response (SVR), and adverse event (AE) data per regimen were extracted into a structured electronic database and analyzed. The network meta-analysis of the estimation was performed by the Bayesian Markov Chain Monte Carlo methods. Results Our search identified 5,278 articles; removing the studies with duplicates and ineligible criteria, a total of 62 studies (comprising 4,554 patients) were included. Overall, the analyses contained more than 2,489 male individuals, at least 202 patients with cirrhosis, and no less than 2,377 patients under hemodialysis. Network meta-analyses of the DAAs found that receiving ombitasvir (OBV)/paritaprevir (PTV)/ritonavir (R) plus dasabuvir (DSV), glecaprevir (G)/pibrentasvir (P), and sofosbuvir (SOF)/ledipasvir (LDV) ranked as the top three efficacy factors for the HCV-infected ESRD patients. Stratified by genotype, the G/P would prioritize genotype 1 and 2 patients with 98.9%−100% SVR, the SOF/DCV regimen had the greatest SVR rates (98.7%; 95% CI, 93.0%−100.0%) in genotype 3, and the OBV/PTV/R regimen was the best choice for genotype 4, with the highest SVR of 98.1% (95% CI, 94.4%−99.9%). In the pan-genotypic DAAs comparison, the G/P regimen showed the best pooled SVR of 99.4% (95% CI, 98.6%−100%). DAA regimens without Ribavirin or SOF showed the lowest rates of AEs (49.9%; 95% CI, 38.4%−61.5%) in HCV-infected ESRD patients. Conclusion The G/P could be recommended as the best option for the treatment of pan-genotypic HCV-infected ESRD patients. The OBV/PTV/R plus DSV, SOF/Velpatasvir (VEL), SOF/Ledipasvir (LDV), and SOF/DCV would be reliable alternatives for HCV treatment with comparable efficacy and safety profiles. Systematic review registration https://www.crd.york.ac.uk/prospero/#searchadvanced, PROSPERO: CRD42021242359.